Intraoperative Radiotherapy in the Treatment of Breast Cancer: A Review of the Evidence - Norman R. Williams; Katharine H. Pigott; Mohammed R. S. Keshtgar (International Journal of Breast Cancer)
The surgical treatment of early breast cancer has evolved from the removal of the entire breast and surrounding tissues (mastectomy) to the removal of the tumour together with a margin of healthy tissue (lumpectomy). Adjuvant radiotherapy, however, is still mainly given to the whole breast. Furthermore, external beam radiotherapy is often given several months after initial surgery and requires the patient to attend the radiotherapy centre daily for several weeks. A single fraction of radiotherapy given during surgery directly to the tumour bed (intraoperative radiotherapy) avoids these problems. The rationale and level-1 evidence for the safety and efficacy of the technique are reviewed.